Aspirin Hypersensitivity and Coronary Artery Disease: A Difficult Clinical Issue (Rhythmos, 2018)
Cardiovascular disease is highly prevalent in modern western societies and aspirin has been established as an irreplaceable drug in such patients. A small but non-negligible number of these patients, manifest hypersensitivity to aspirin and /or other non-steroidal anti-inflammatory drugs (NSAIDs), which can take different forms depending on the underlying pathophysiology and clinical variability. In this brief communication, we review the types of hypersensitivity to NSAIDs, the diagnostic steps and its management, focusing on desensitization protocols in patients who require coronary interventions and long-term salicylate administration. Rhythmos 2018;13(2);30-34.
Keywords: coronary artery disease; aspirin; hypersensitivity; acute coronary syndrome; myocardial infarction